MANAJEMEN PEMBELAJARAN BERBASIS E-LEARNING DI MASA PANDEMIC COVID 19 - Futri Elizah; Idi Warsah; Jumira Warlizasusi; Riza Faishol; Lukman Asha (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2022)
One of the learning models that can be used during the covid-19 period is e-learning. Accordingly, the purpose of this study is to create a picture of the application of e-Learning in the process of teaching and learning activities at SMAN 4 Rejang Lebong. The qualitative method was adopted in this study. Data were gathered through interviews and documentation techniques. Following data collection, the data were analyzed using the Miles et al approach, which comprised data reduction, recitation, and conclusion drawing. This study drew the following conclusions: The management of e-Learning at SMA Negeri 4 Rejang Lebong was going well, as evidenced by adequate infrastructure and financing. However, if it was not supported by adequate human resources, it would be constrained and its implementation would not be maximal. To the objectives as desirable, the school’s serious efforts and hard work were required. The constraints of e-learning implementation extended to human resources, communication networks, difficulty in obtaining affective and psychomotor assessments, time sharing, lack of parental motivation, and students’ values below the standard. As the solution, teachers should explore their abilities and creativities to seek innovations, and there must be positive and strong principal leadership, continuous monitoring, student responsibility, and incentives.